ANOMALOUS ORIGIN OF THE LATERAL THORACIC ARTERY: CASE REPORT - Silva, Victor Eduardo Maia; Amorim, Rodrigo Cesar das Neves; de Rezende, Fabio Moniz (ARACÊ, 2025)
The arterial supply of the lateral wall of the chest is provided by branches of the axillary artery (AA), which is subdivided into three parts by the pectoralis minor muscle. Regarding the anatomical variation in the branches originating from the artery, axillary, when if treats from the artery thoracic side emerging as a branch of the subscapular artery has an incidence rate of approximately 3.9% (Loukas et al. , 2013). In this way, the subscapular artery generates its terminal branches described in the literature and also gives off the lateral thoracic artery, forming a trifurcation. Thus, this article aims to report an anatomical variation in the origin of the lateral thoracic artery of one individual of sex masculine, with focus in the explanation anatomical of the findings. Variations in the axillary artery and its branches are common and many of which they are documented in the literature, being this found described in the literature with an incidence of 3.9% (Gravante, 2012), this finding being important in treatment prior the procedures invasive from the region axillary.